2001
DOI: 10.1073/pnas.031383098
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of DNA in the equilibrium between OmpR and phosphorylated OmpR mediated by EnvZ in Escherichiacoli

Abstract: Escherichia coli modulates its porin expression through a histidine kinase, EnvZ, and its cognate response regulator, OmpR. EnvZ is a bifunctional enzyme that possesses both OmpR kinase and phosphorylated OmpR (OmpR-P) phosphatase activities and thus controls the cellular level of OmpR-P. In an in vitro-assay system, the addition of OmpR to the reaction mixture consisting of the cytoplasmic domain of EnvZ (EnvZc) and ATP produces a barely detectable amount of OmpR-P because of the dual activities of EnvZ. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The only exception was that the OmpR TF family of pathogenic Leptospira species ( L. interrogans and L. borgpetersenii ), which was larger than that of L. biflexa . Considering that the OmpR TF was first defined as a regulator of outer membrane porin genes ( ompC and ompF ) in E. coli [78] , [79] , it is possible that the leptospiral OmpR TFs were also involved in the regulation of the porins or other membrane proteins. Pathogenic Leptospira may regulate OMPs more efficiently than non-pathogenic L. biflexa .…”
Section: Resultsmentioning
confidence: 99%
“…The only exception was that the OmpR TF family of pathogenic Leptospira species ( L. interrogans and L. borgpetersenii ), which was larger than that of L. biflexa . Considering that the OmpR TF was first defined as a regulator of outer membrane porin genes ( ompC and ompF ) in E. coli [78] , [79] , it is possible that the leptospiral OmpR TFs were also involved in the regulation of the porins or other membrane proteins. Pathogenic Leptospira may regulate OMPs more efficiently than non-pathogenic L. biflexa .…”
Section: Resultsmentioning
confidence: 99%
“…We chose to study the OmpR response regulator binding because it is a well-characterized protein and its target promoter regions are known in detail. ,,, In E. coli, OmpR and its cognate sensor kinase, EnvZ, control the expression of the outer membrane porin proteins, OmpC and OmpF. In response to changes in environmental osmotic pressure, OmpR binds in a hierarchical fashion to the promoter regions of the ompF and ompC genes. ,,, The promoter regions for the OmpF and OmpC proteins consist of multiple protein binding regions, designated F1, F2, F3, F4, and C1, C2, C3 (Figure A), each approximately twelve nucleotides long. Two OmpR molecules bind to each site and then interact with the alpha subunit of RNA polymerase to control transcription .…”
Section: Resultsmentioning
confidence: 99%
“…This form of the protein binds to high affinity sites on the ompF gene (F1, F2) and thus causes expression of the OmpF porin protein. As the osmotic pressure of the environment increases, the level of the phosphorylated form of the protein (OmpR-P) increases, and additional low affinity sites are occupied (C1, C2, C3, F3, and F4) as the protein becomes more active. ,, Binding to the low affinity F4 site results in transcriptional repression of the OmpF protein, while binding to the low affinity sites on the ompC gene results in transcriptional activation of the OmpC protein 1 Schematic presentations.…”
Section: Resultsmentioning
confidence: 99%
“…OmpF is the key ligand for susceptibility (8,42), but other genes have been identified that are requisite for susceptibility to MccPDI (ompR, atpA, atpF, atpE, atpH, dsbA, and dsbB [8]). OmpR regulates the expression of ompF as part of the EnvZ/OmpR two-component osmoregulatory system (42)(43)(44). The roles of ATP synthase (atpA, atpF, atpE, and atpH) and thiol-disulfide interchange protein (dsbA and dsbB) in MccPDI susceptibility remain unknown (8,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%